Muscle strength (Fiep Bulletin - online, 2015)
Dr. Hunsicker summarizes the instruments for strength testing in an article published in Research Quarterly. According to this the first person who used the instrument named “dynamometer” was graham in England. It is also said that French anthropologists had devised dynamometers for measuring muscle strength in 1600’s.